Morphofunctional study of the junction between the left atrium and the pulmonary veins in patient with pulmonary hypertension - Cavalcanti,Jennecy Sales (2001)
OBJECTIVE: To study the arrangement of the myocardial fiber bundles at the pulmonary venous left atrial junction in patients with pulmonary hypertension, and to discuss the pathophysiological importance of this element in the etiology of acute pulmonary edema. METHODS: We obtained 12 hearts and their pulmonary vein extremities from postmortem examinations of patients with the anatomicopathological diagnosis of acute pulmonary edema. The specimens, which had no grossly visible morphological cardiac alterations, were fixed in 10% formalin, and the muscular arrangement of the pulmonary venous left atrial junctions was analyzed. This material was then isolated, embedded in paraffin, underwent serial cutting (50 µm of thickness), and was stained with Azam's trichrome. RESULTS: We observed in our specimens that: a) the myocardial fiber bundles that originate in the atrial wall and involve the openings of the pulmonary veins were fewer than those observed in healthy material; b) the myocardial fiber bundles that extend into the pulmonary veins were shorter than those found in material originating from individuals with no pulmonary hypertension. CONCLUSION: Anatomical changes that result in a reduction in the amount of myocardial fiber bundles in the pulmonary venous left atrial junction, isolated or associated with other factors, may be the cause of disorders in pulmonary circulation, leading to an increase in pulmonary venous pressure, and, consequently, to acute pulmonary edema.